Relationship between grit and subjective career success in teacher - Putri, Shafira Salsabilla Suryono; Ingarianti, Tri Muji (Jurnal Ilmiah Psikologi Terapan, 2024)
Choosing a career as a teacher is a long journey because individuals must be ready to serve for a lifetime to educate the nation's generation. In other words, the teacher needs to define their subjective career success and have an unyielding personality, such as grit, to remain consistent in achieving subjective career success. This study aims to determine the relationship between grit and subjective career success in teachers. This correlational quantitative study involved 300 teachers, consisting of 85 male and 215 female teachers aged 20 to 54 years. Data were collected using non-probability quota sampling with the Grit-O Scale and Subjective Career Success Scale. The results of data analysis showed that grit was significantly associated with eight dimensions of subjective career success in teachers, with a p-value of <.001. The implication of this research is that teachers are expected to be able to help teachers build persistence and consistency of interest in their careers so that they will be able to overcome all obstacles and failures in their careers.